Circulatory support for prolonged electro-mechanical standstill in fulminant pediatric myocarditis. Issue 6 (June 2021) - Deshpande, Shriprasad R; Willett, Renee C; Ramakrishnan, Karthik; Peer, Syed Murfad; Sinha, Pranava
Pediatric patients with fulminant myocarditis can rarely present with complete heart block with severe hemodynamic compromise, cardiac arrest and require circulatory support. Additionally, patients with cardiac dysfunction that require extracorporeal membrane oxygenation (ECMO) support sometimes develop cardiac stun or standstill. These factors are associated with extremely poor survival. We present a case of fulminant myocarditis presenting with dense heart block, no ventricular electrical activity resuscitated with ECMO that developed prolonged cardiac standstill. We present the clinical course, management including ECMO followed by biventricular assist devices, pacing and review supporting literature. We hope that the case will highlight challenges in management and decision making in such patients.